Negotiation Of Self And Identity: A Cixousian Study Of Gender And Sexuality In The Selected Works Of Indian Fiction In English By Indian Woman Writers - Anuar, Nur Ain Nasuha (2024)
Within the literary sphere of Indian Fiction in English, Indian woman writers of home country and diaspora have emerged to bring forth women’s narratives about gender and sexuality through the female characters in their writings. The portrayal within these works emphasizes conflicting circumstances faced by female characters as a result of clashing traditional and contemporary values about gender and sexuality affecting the (re)formation of self and identity. In this study, three novels of Indian Fiction in English have been selected: one written by Indian woman writers from home country The Ministry of Utmost Happiness by Arundhati Roy, and two written by Indian woman writers from diaspora Before We Visit the Goddess by Chitra Banerjee Divakaruni and Well-Behaved Indian Women by Saumya Dave. This study intends to examine the strategies employed by the female characters in resisting heteropatriarchal normativities and the different ways the female characters redefine their self and identity in the selected novels. Using Hélène Cixous’s French feminist framework, the notions of “the feminine”, “the other”, other bisexuality and écriture feminine Cixous proposes are applied through Braun’s and Clarke’s six-step thematic analysis. The findings of the study reveal that the female characters in the three selected novels have demonstrated covert manifestations of resisting heteropatriarchal normativities such as through silence and subversion of feminine activities. In addition, the female characters have reconstructed their sense of self and identity by reclaiming their gender and sexuality.